Hubungan Antara Kecerdasan Emosional Dengan Keterampilan Berpikir Kritis Pada Pembelajaran Matematika Siswa di Madrasah Tsanawiyah - Risa, Fanti; Mauliddin, Mauliddin (Mathematic Education Departement, State Islamic University of Mataram, 2022)
This study aims to determine the relationship between emotional intelligence and critical thinking skills in mathematics learning for students of class VII MTs. Muhammadiyah Nangapanda for the academic year 2021/2022. This research uses a quantitative approach with a correlation design. With data collection techniques using test methods, questionnaires, and documentation. In answering the sample using purposive sampling technique with a sample of 22 people in one class, namely class VII. Based on the results of the analysis that has been carried out using pearson product-moment correlation analysis, obtained the correlation coofynent r = 0.426 and the relationship belongs to the sufficient category. This shows that accepted and rejected because or , so it can be said accepted and rejected with the large contribution that emotional intelligence gives to critical thinking skills on mathematics learning is only 18.14%. The results obtained from this study show that there is a relationship between emotional intelligence and critical thinking skills in mathematics learning but in the sufficient category, so it can be concluded that there is a relationship between emotional intelligence and critical thinking skills in mathematics learning of class VII MTs. Muhammadiyah Nangapanda students for the academic year 2021/2022